(untitled) (ouvirOUver, 2018)
Nesta entrevista com Marjolaine Beuzard, a curadora de arte de origem francesa Catherine Bompuis propõe uma leitura do contexto da arte brasileira entre 1940 e 1980. Ela relata o modernismo brasileiro, aponta as especificidades da arte brasileira dos meados do século 20, e analisa as ideias de Mario Pedrosa sobre a arte, a sociedade e a política. A originalidade dessa entrevista entremeia-se com o prazer de saborear as trajetórias da arte contemporânea brasileira na perspectiva de um olhar externo e abrangente, que tece relações entre as cenas artísticas européia e latino-americana. ABSTRACT In this interview with Marjolaine Beuzard, the independent french curator Catherine Bompuis analyses the context of Brazilian art between 1940 and 1980. She talks about Brazilian modernism, points out the specificity of Brazilian art from the mid-20th century, and expose Mario Pedrosa’s ideas about art, society and politics. The originality of this interview is interspersed with the pleasure of savoring the trajectories of contemporary Brazilian art in the perspective of an external and comprehensive look that links European and Latin American artistic scenes. KEYWORDS Brazilian neo-concretism, Mario Pedrosa, Brazilian contemporary art